SYSTEM LITERATURE REVIEW : PERAN MAHASISWA DALAM MENSUKSESKAN PENGELOLAAN LINGKUNGAN BERKELANJUTAN BERBASIS PROGRAM GREEN CAMPUS - Dien Maulinda, Arin; Fradito, Aditia; Yetri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students have a very important role in a campus program including in supporting sustainable management and the Green Campus program. This study aims to analyze the role of students in making a sustainable environment based on the Green Campus program a success. The researcher used the System Literature Review method from various sources related to this study. Based on the literature analysis, students function as agents of change, social control, iron stock and moral force in promoting environmental awareness. Environmental management includes planning, implementation, and supervision, with standards such as ISO 14001 and EMAS to improve performance. A sustainable environment emphasizes the optimal use of resources to meet current and future needs, in line with the sustainable development goals (SDGs). The Green Campus program in Indonesia, as initiated by UI Green Metric, integrates environmental, economic, and social aspects to create an environmentally friendly campus. The results of the study indicate that active participation of students and academics in this program is very important to achieve sustainability and maintain environmental sustainability, as well as strengthen social relations.